Indian Gaming: The Declining Democratic Advantage in State Legislative Elections. Issue 6 (December 2015) - Garner, Andrew; Skopek, Tracy
Abstract : As policy making for Indian gaming and other tribal issues has shifted from the federal government to state politics and state legislatures over the past several decades, the role of American Indians in the electoral process in state legislative elections deserves greater scholarly attention. We examine changes in voting patterns among state legislative elections over a 40‐year period for districts with and without casinos. In the past, Democrats held a large advantage in casino districts both in terms of the two‐party vote share and in terms of incumbents running unopposed when seeking reelection. Since the 1990s, this traditional Democratic advantage has largely disappeared to a point where the two parties compete at rough parity in these districts. In several states, American Indians represent a sizeable and potentially influential voting bloc. Related Articles: Pearson‐Merkowitz, Shanna. 2012 . "Aqui No Hay Oportunidades: Latino Segregation and the Keys to Political Participation ."Politics & Policy 40 (2 ):258 –295 .http://onlinelibrary.wiley.com/doi/10.1111/j.1747-1346.2012.00349.x/abstract Adams, Brian E. 2012 . "Citizens, Interest Groups, and Local Ballot Initiatives ."Politics & Policy 40 (1 ):43 –68 .http://onlinelibrary.wiley.com/doi/10.1111/j.1747-1346.2011.00336.x/abstract Sullivan, Jas M., Lesa Hatley Major, Kirby Goidel, andDavid Kurpius .2009 . "The Role of an African‐American Candidate on Psychological Engagement and Political Discussion in a Local Election ."Politics & Policy 37 (2 ):289 –308 .http://onlinelibrary.wiley.com/doi/10.1111/j.1747-1346.2009.00173.x/abstract Related Media: Bogardus, Kevin. 2013 ."Casino Lobbyist: Time to Go on the Offensive." The Hill .http://thehill.com/policy/technology/327241-casino-lobbyist-time-to-go-on-offense Parti, Tarini .2015 . "Tribal Casino Fight Tests Lobbying Clout." Politico.com. http://www.politico.com/story/2015/05/tribal-casino-fight-lobbying-117992 Jones, Harriet .2015 . "Tribes Lobby Hartford‐Area Businesses on Expanding Gaming." WNPR.org. http://wnpr.org/post/tribes-lobby-hartford-area-businesses-expanded-gaming#stream/0